Elephant Endotheliotropic Herpesvirus Infection in Asian Elephants (Elephas maximus): A Review - Alkausar, Triawan; Kamelia, Marlina; Yosilia, Rani; Anisya, Shinta; Satitiningrum, Yuni (Program Studi Pendidikan Biologi, FKIP Unpas,, 2024)
Elephants are charismatic exotic animals. As the largest land animal on the earth, their maximum weight can reach more than 7 tons and 4 meters in height. Apart from their exoticness, however, elephants, particularly Asian elephants are now losing more than 70% of their habitat. As a result, the International Union for Conservation of Nature (IUCN) has red-listed Asian elephants as the critically endangered animal. Various conservation efforts have been implemented, such as translocation of the elephants, control of poaching, educational campaigns, and research. Nonetheless, over the past two decades, Elephant Endotheliotropic Herpesvirus (EEHV), a newly emerging disease has caused a serious threat to Asian elephants’ health worldwide. The virus causes a rapid, acute, and fatal haemorrhagic disease as the major clinical manifestation in adult Asian elephants and particularly in juvenile elephants in both wild and captive populations. This article provides a literature review regarding the EEHV infection in Asian elephants.